2016
DOI: 10.1590/1807-1929/agriambi.v20n1p9-15
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of non-exchangeable potassium forms and its accumulation in corn plants

Abstract: A B S T R A C TThe state of Paraíba, Brazil, has soils from well-to poorly-developed, in which potassium (K) is found in different levels, forms and, consequently, with varying availability to plants. The objective of this study was to evaluate the contribution of non-exchangeable K forms to corn plants in 12 soils from Paraíba state, along four successive cycles. The experimental design was completely randomized block with three replicates and the 24 treatments consisted of the combination between two K level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
1
2
0
3
Order By: Relevance
“…According to Velde and Peck (2002), these limits are determined mainly by the mineralogy of soils. The results presented here for the exchangeable K and non-exchangeable K in the soils (Figure 4) confirmed the results reported by Fraga et al (2009), Vieira et al (2016) and Rosolem, Vicentini and Steiner (2012). These authors showed that the non-exchangeable K pool could maintain or even enhance soil exchangeable K reserves in the long term.…”
Section: Soil Potassium Poolssupporting
confidence: 90%
See 2 more Smart Citations
“…According to Velde and Peck (2002), these limits are determined mainly by the mineralogy of soils. The results presented here for the exchangeable K and non-exchangeable K in the soils (Figure 4) confirmed the results reported by Fraga et al (2009), Vieira et al (2016) and Rosolem, Vicentini and Steiner (2012). These authors showed that the non-exchangeable K pool could maintain or even enhance soil exchangeable K reserves in the long term.…”
Section: Soil Potassium Poolssupporting
confidence: 90%
“…In lowland soils of Rio Grande do Sul, Brazil, Fraga et al (2009) found that non-exchangeable K contribution to the K nutrition of rice plants ranged 12 to 72% in the treatments no fertilized and fertilized with K fertilizer, respectively. The exploitation of K pools initially considered nonexchangeable for plants has been commonly reported in the literature, even in scenarios involving K fertilizer application (VIEIRA et al, 2016;LANA, 2018). Rosolem, Vicentini, and Steiner (2012) found that the nonexchangeable K pools were the main sources of the nutrient for successive cropping of ruzigrass [Urochloa ruziziensis (Syn.…”
Section: Non-exchangeable K Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todavia, elevadas quantidades de K foram fornecidas pela adubação potássica, bem como pela aplicação de vinhaça via irrigação. Além disso, diversos autores já observaram que formas não-trocáveis de potássio também podem contribuir, expressivamente, para o suprimento desse elemento às plantas (KAMINSKI et al, 2010;ÖBORN et al, 2010;VIEIRA et al, 2016;VIEIRA et al, 2017), principalmente quando verifica-se a dominância de argilominerais 2:1, como mica e interestratificados micavermiculita com hidroxi-Al entrecamadas (VHE) ou mica-esmectita e esmectita com hidroxientrecamadas muito comuns em Vertissolos. Esses argilominerais podem constituir fontes importantes de K no solo (ERNANI et al, 2007;FRAGA et al, 2009), Na extração total de Ca, observaram-se valores de 245 e 139 kg ha -1 , aos 352 e 385 dias respectivamente, com média de 89 kg ha -1 .…”
Section: Oooolineunclassified
“…Como estas formas de K estão em equilíbrio, quando o K solúvel é absorvido pela planta ou perdido do solo por lixiviação, este equilíbrio é mantido mediante a liberação de K trocável para a solução do solo. Quando a concentração do K trocável atinge valores muito baixos, ocorre liberação de K não trocável para as formas trocável e solúvel, o que possibilita o desenvolvimento das plantas, mesmo em solos com baixos teores de K trocável e K solúvel (Kirkman et al, 1994;Kaminski et al, 2007;Medeiros et al, 2014;Vieira et al, 2016).…”
Section: Introductionunclassified